CARTILHA INFORMATIVA PARA PREVENÇÃO DOS AGRAVOS DA SÍFILIS CONGÊNITA E OUTRAS INFECÇÕES SEXUALMENTE TRANSMISSÍVEIS - Beck, Elisiane Quatrin (2017)
Introduction: Syphilis remains a serious public health problem, with increasing numbers of cases in pregnant women and their partners, which favors the increase of congenital syphilis. This fact demonstrates the need for more effective prevention strategies. Congenital syphilis generates a high financial cost for the health system, besides a great social impact related to the sequels of the disease. Besides these factors, they cause emotional shock to the mothers of newborns with congenital syphilis, justifying the research in this area. Goals: Understanding maternal perceptions of congenital syphilis and the health care of these newborns. As specific objectives: To identify the knowledge of the mothers of newborns with congenital syphilis about the disease; To know the care of the mothers of newborns with congenital syphilis in relation to treatment and monitoring; Creating informational material on congenital syphilis and other Sexually Transmitted Infections, as well as health problems and care of these newborns. Meth-odology: This is a qualitative research of a descriptive nature, developed in a medium-sized hospital in the city of Paranoa / DF, in the period from March to August 2017. Fifteen women, mothers of newborns with congenital syphilis who were in the treatment phase of their children in the hospital's maternity ward participated of the research. Results: The data showed that the interviewees had unfavorable social conditions. Although it is not a disease restricted to the less favored layers, these results indicate a higher social and reproductive vulnerability of these women. The participants of the study reported the performance of prenatal care in the appro-priate period, that is, in the first trimester. Although the data points to an adequate prenatal search, a favorable outcome of syphilis treatment was not assured, generating the diagnosis of Congenital Syphilis in the baby. The complexity of the treatment for congenital syphilis, added to the lack of knowledge about the disease, may explain the limitation of who have recently given birth regarding comprehension and feelings. Product: Booklet with information on Con-genital Syphilis and other Sexually Transmitted Infections to support mothers and their part-ners as well as sexually active adults with the aim of reducing new cases of congenital syphilis and other Sexually Transmitted Infections. Final considerations: With the accomplishment of this work, it was realized that for a better understanding of the measures to prevent the conse-quences of Congenital Syphilis, changes in attitude are necessary in health services. Initially it is suggested that the changes involve proactive actions by the public health system and health professionals. The context of the Network of Health Care can broaden its vision regarding social, economic and health education actions. In this way we can contribute more effectively to achieve better results in the index of cases of congenital syphilis in Brazil.